Thyroid Peroxidase Revisited – Whatʼs New? - Godlewska, Marlena; Gawel, Damian; Buckle, Ashley M.; Banga, J. Paul (Hormone and Metabolic Research, 2019)
Thyroid peroxidase (TPO) is an enzyme that participates in thyroid hormone biosynthesis. TPO is also a major autoantigen in autoimmune thyroid diseases (AITD). In this review, we summarize the latest developments in the field of TPO research. We present the current understanding of immunodominant serologic determinants, frequency of TPO-specific autoantibodies in the population, as well as genetic and environmental factors contributing to their development. Moreover, we report recent progress in the clinical utilities of TPO autoantibody testing, including thyroid dysfunctions and extra-thyroidal disorders.
Keywords: antibodies to thyroperoxidase; autoantibodies; autoimmunity; autoimmune thyroiditis; Gravesʼ disease; Hashimoto’s disease